Transitions from vocational qualifications to higher education : examining inequalities - Banerjee, Pallavi Amitava; Myhill, Debra (Emerald Publishing Limited, 2019)
Very few students with vocational qualifications progress into the world of Higher Education. Many drop out of education altogether and take up entry level jobs with decreased financial prospects. This trend is worrying as the lack of students with vocational backgrounds applying to University acts as a barrier to social mobility.This book, informed by the research findings from Transforming Transitions - a collaborative project involving further education colleges, sixth form centres and Universities - addresses key concerns such as the background of those with vocational qualifications, the success of these students at university and any issues they may encounter in higher education. By analysing national datasets and conducting interviews with students and tutors across sixth form colleges and Universities, this important text discusses the socio-economic benefits gained from the vocational provision and transition to higher education. By highlighting the need to develop inclusive pedagogies and proposing practical recommendations, this book will prove to be an invaluable resource for Educational leaders, researchers and practitioners in higher education.